Two Perspectives of Mental Distress. - Cornelius, John Thor (Psychoanalytic Inquiry)
This article explores an imbalance between two perspectives on mental distress. The Broken Brain perspective sees mental distress as largely caused by discrete mechanical failures of organic brain function. In tension with this, the Symphonic perspective of mind (encompassing, but not limited to, psychodynamic models) refers to a non-local, wholistic and distributed process spread across the entirety of the mental capacity in which mental distress results from the impacts of tragic life experience on the normally functioning mind. While overlapping in some areas, these two perspectives often lead to dramatically different ways of understanding and treating mental distress. While the Broken Brain perspective has had preeminence in recent decades, it is suffering from increasingly serious scientific and clinical obstacles. Conversely, the Symphonic perspective is increasingly supported both theoretically and clinically by emerging scientific evidence as an efficacious, reasonable, and cost-effective treatment approach.